2021
DOI: 10.3389/feduc.2021.694516
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Influences of STEAM-Based Curriculum on Scientific Creativity of Elementary School Students

Abstract: Up until now, there have been several different viewpoints on creativity in general and creativity in the science field in particular. Furthermore, STEAM (science, technology, engineering, arts, and mathematics) education is increasingly successful and widespread around the world; however, few studies on its impact on scientific creativity exist. As a result, research on the influence of STEAM-based curriculum on students’ scientific creativity is critical. Elementary school students were chosen to be investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In a previous study, Tran et al (2021) demonstrated that the STEAM-based curriculum could increase students' scientific creativity. In particular, in the three components of scientific creativity (fluency, flexibility, and originality), the fluency and flexibility components showed a significant improvement; and the effects of the STEAM-based curriculum on various genders are obviously similar.…”
Section: Hypothesesmentioning
confidence: 98%
“…In a previous study, Tran et al (2021) demonstrated that the STEAM-based curriculum could increase students' scientific creativity. In particular, in the three components of scientific creativity (fluency, flexibility, and originality), the fluency and flexibility components showed a significant improvement; and the effects of the STEAM-based curriculum on various genders are obviously similar.…”
Section: Hypothesesmentioning
confidence: 98%
“…However, contrasting outcomes were reported by Tran et al (2021), who examined the impact of a STEAM-based curriculum on elementary students' scientific creativity. Despite finding significant improvements, their methodology and interventions provide a different perspective on how educational strategies may influence creativity differently depending on contextual factors.…”
Section: Effectiveness In Increasing Creativitymentioning
confidence: 99%
“…Current tools and interventions, such as Student Activity Sheets (SAS) and Scientific Creativity Tests (SCT), have not been universally adopted or validated in different educational contexts, limiting their potential impact (Büyük & Koç, 2020;Genek & Küçük, 2020;Nacaroğlu & Mutlu, 2023). Furthermore, the effectiveness of these tools in different cultural and educational settings has not been adequately explored, raising questions about their generalizability and adaptability (Mercan & Köseoğlu, 2022;Tran et al, 2021). This is particularly important as educational frameworks and student demographics vary significantly across regions, necessitating a more customized approach to implementing and evaluating educational innovations (Akcanca & Ozsevgec, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different educational backgrounds of teachers and the limitations in increasing literature reviews have an impact on reducing students' creative thinking skills because learning is still monotonous and less interesting (Wilsa et al, 2017). There is no innovation in the learning program yet, moreover the material used is only the result of downloading on the internet, so the learning program used is not based on real problems that occur in life and the learning references used have not trained students' creative thinking skills (Tran et al, 2021) .…”
Section: Introductionmentioning
confidence: 99%